THE CASE OF MOHAMMED AISHA: THE EFFORTS IN PROTECTING SEAFARERS AGAINST ABANDONMENT - Melania Fidela Ghaida; Tobias Binsar Ezra (Padjadjaran Journal of International Law, 2021)
The abandonment case of Mohammed Aisha is a case that occurred in 2017, where the ship MV Aman was detained in the Egyptian port of Adabiya and caused a situation where Mohammed Aisha was trapped on the ship due to the failure of the shipowners. This then led to the case of the abandonment of seafarers. In this case, MLC 2006 is the instrument that covers regulation towards abandonment and seafarers' rights. This study was made to provide a broader and more detailed perspective related to cases of abandonment and MLC 2006. The goal of this research is to clarify matters that are unclear related to the regulation that is mentioned in MLC 2006, such as the vague regulation of who is in charge between flag states, port states, and nationals of seafarers in the case of the abandonment of seafarers in both theory and practice. Apart from clarifying the unclear matters of who is in charge of the three states mentioned previously, this research will elaborate even further regarding the International Transport Workers' Federation (ITF) role in advocating the repatriation of the abandoned seafarers. This research revealed that the 2006 MLC has not been very effective in protecting the rights of seafarers and that the obligation for repatriation lies within the flag state; however, in its practice, when a flag state fails to carry its obligation, then the port state and the origin country of the seafarers with the help from ITF shall take that roll.